Patient safety: Prevention during care - Vaidya, A (Kathmandu University Medical Journal, 2010)
DOI: 10.3126/kumj.v8i2.3547 Kathmandu University Medical Journal (2010), Vol. 8, No. 2, Issue 30, 151-152